1984
DOI: 10.1103/physrevlett.52.1645
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Related Optical Defects in Silicon Implanted with the Noble Gases He, Ne, Ar, Kr, and Xe

Abstract: A unique class of electronic-vibronie photoluminescence spectra in silicon is observed exclusively after noble-gas ion implantation and partial annealing. Characteristic features are mass-dependent systematic line shifts, systematic behavior in the defect formation and annealing, and the common trigonal defect symmetry. The spectra are closely related with the previously studied I\ (1.018-eV) spectrum emitted by an intrinsic lattice defect. It is concluded that the noble gases are incorporated into the intrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…The energy shift between the I and the Ar defect is due to the interaction of implanted Ar atoms with the defect responsible for the II-line. [9] We have already shown that similar defects can also be formed by ion beam etching with other noble gases such as Ne, Kr and Xe. [5,6) The PL-lines of the different noble gases show similar small energy shifts from the Ii luminescence.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The energy shift between the I and the Ar defect is due to the interaction of implanted Ar atoms with the defect responsible for the II-line. [9] We have already shown that similar defects can also be formed by ion beam etching with other noble gases such as Ne, Kr and Xe. [5,6) The PL-lines of the different noble gases show similar small energy shifts from the Ii luminescence.…”
Section: Discussionmentioning
confidence: 92%
“…Spectrum (b) shows the same sample as in (a) after it was etched for 15 minutes in an Ar ion beam with an energy of 1100 eV and then annealed for 30 minutes at 350 0 C. The spectrum is labeled as in Ref. 9. A very small 1 1 -line is present as well as the Aro no phonon transition and its various local phonon replicas.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is most efficiently produced by ion or neutron bombardment, but can also be produced by other forms of radiation. Magnetic field and uniaxial stress measurements have shown that the I1 ground state is non-degenerate, and that the defect has C 3 , symmetry [3][4][5]. It has a total binding energy of 137 meV, and the temperature dependence of the PL intensity has an Arhenius quench energy (t hermal binding energy) of about 50 meV [4].…”
Section: Introductionmentioning
confidence: 97%
“…neutrons, ions, protons) [ [2]. Existence of W line is not dependent on the presence of any impurity, although its energetic position has been found to be sensitive to the presence of the nobel-gass atoms [3], [4]. It is generally accepted that W-centre arises from agglomeration of intrinsic species.…”
Section: Introductionmentioning
confidence: 99%